Motivasi Wisatawan Mengunjungi Destinasi Wisata Dark Tourism - Rusmiati, Debi; Andari, Rini; Waluya, Bagja (Tourism and Hospitality Essentials Journal, 2022)
AbstrakDestinasi wisata yang terkait dengan kejadian kelam (dark tourism) mendapatkan banyak perhatian dalam dua puluh tahun terakhir. Pertanyaan mengenai apa motivasi wisatawan yang berkunjung ke destinasi wisata dark tourism terus dikaji. Artikel ini bertujuan untuk memahami apa saja motivasi pengunjung yang berkunjung ke destinasi dark tourism. Studi literatur terkait kajian-kajian yang berkenaan dengan dark tourism digunakan untuk memahami motivasi pengunjung. Berdasarkan literatur, ditemukan sembilan jenis motivasi yang muncul pada aktivitas wisata dark tourism, yaitu Experience, History, Education, Culture and Identity, Remembrance, Thrill-seeking, Site, Exhibits, Death and Dying. Selain itu, ragam daya tarik yang terkait dengan dark tourism di Desa Ciburial Kabupaten Bandung juga didiskusikan. Kajian ini memberikan pemahaman mengenai ragam motivasi wisatawan dalam mengunjungi destinasi wisata dark tourism, khususnya di Indonesia.Keywords: dark tourism, motivasi, destinasi wisataAbstractTourist destinations related to dark tourism have received a lot of attention in the last twenty years. The question of what is the motivation of tourists who visit dark tourism destinations continues to be studied. This article aims to understand what are the motivations of visitors who visit dark tourism destinations. Literature studies related to studies related to dark tourism are used to understand the motivation of visitors. Based on the literature, nine types of motivation were found in dark tourism activities, namely Experience, History, Education, Culture and Identity, Remembrance, Thrill-seeking, Site, Exhibits, Death and Dying. In addition, various attractions related to dark tourism in Ciburial Village, Bandung Regency were also discussed. This study provides an understanding of the various motivations of tourists in visiting dark tourism destinations, especially in Indonesia.Keywords: dark tourism, motivation, tourist destinations